Sistem Penjadwalan Kunjungan Biro Marketing Kalbis Institute Berbasis Website - Rizka Aulia Safitri; Mira Ziveria (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The distribution of the visit schedule of the Kalbis Institute Marketing Bureau is still conventional. This research is done with the aim to create a scheduling that all officers will get in the same time using a prototype system development method which includes system analysis using cross functional Flowwchart, system design with unified modelling language modeling, development using Hyrpertext Processor (PHP), programming language and database with My Structure Query Language (MySQL), and system testing with black box testing. The results of this study are a scheduling system that can be used to make scheduling up to automated reports.